Penggunaan Instagram Sebagai Sistem Informasi Digital dan Media Promosi di Universitas - Tan Evan Tandiyono; Mahfud Eko Prasetyo; Erlangga Rifqi Syahputra; Muhammad Faiz Ilham; Himawan Prasetyo Purnomo (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study examines the use of Instagram as a digital information system and promotional media in a university context. Employing a descriptive qualitative approach, data were collected through direct observation of the university’s official Instagram account and semi-structured interviews with three informants, consisting of one campus Instagram administrator and two active students. The findings indicate that Instagram functions not only as a channel for disseminating academic information, announcements, and campus activities, but also as a strategic promotional medium that shapes institutional image and public perception. Content integration between informational and promotional messages allows universities to communicate more efficiently while maintaining audience engagement through visual storytelling and interactive features. The study also reveals that consistent content management, visual coherence, and responsive interaction contribute to increased trust and participation among students. Overall, Instagram emerges as an integral component of digital communication strategies in higher education, supporting transparency, branding, and relationship building with stakeholders. These findings highlight the importance of managing social media platforms systematically to maximize their potential as digital information systems and promotional tools for universities.